Techno-economic analysis of a hybrid electrodialysis–batch reverse osmosis process for brackish water desalination - Dipak Ankoliya; Anurag Mudgal; Manish Kumar Sinha; Vivek Patel; Jatin Patel (Aqua, 2023)
Hybridization of electrodialysis (ED) and batch reverse osmosis (BRO) process is used to reduce the brine volume and water production cost. The ED process has the benefit of high water volume recovery in brackish water desalination, while reverse osmosis can produce pure water at a low production cost. Here, a simple hybrid process layout is preferred in which the ED process is kept in the reject stream of the BRO process and permeate from both ED and BRO is mixed. Recovery of the ED process is kept at 70% which can decide the blending ratio of ED and BRO permeates. The capital cost and operating cost of ED and BRO processes are used to calculate water production cost. The water production cost from the hybrid ED–BRO process is found to be 0.22 $ m−3 of freshwater when the feed concentration is 1,100 ppm. The cost increases from 0.20 to 0.34 $ m−3 with feed concentration from 1,000 to 2,000 ppm. In the cost, a major portion comes from the capital equipment in which the highest contributor is the membrane for both ED and BRO processes. HIGHLIGHTS Designing hybrid electrodialysis and batch reverse osmosis process for brackish water desalination.; Effect of feed concentration on the freshwater cost of the hybrid ED–BRO process.; The hybrid process increases water recovery and has 0.22 $ m−3 freshwater cost at 1,100 ppm feed concentration.;